A Global Scale Analysis of River Flood Risk of UNESCO World Heritage Sites - Arrighi, Chiara (Frontiers in Water, 2021)
Floods can significantly affect Cultural Heritage with consequences that might not easily be repaired, given the unicity of this type of exposed asset. Cultural flood losses are both tangible and intangible since communities rely on cultural heritage for its historical, spiritual, aesthetic and socio-economic values. This work aims at examining river flood risk of UNESCO tangible World Heritage (UNWH) sites to identify the most at risk assets with a matrix approach entailing hazard, exposure and vulnerability at a global scale. A distinction is made between natural sites, for which only hazard and exposure are assessed, and cultural and mixed sites. Hazard is evaluated by using the river flood maps at global scale developed by JRC for six probabilistic scenarios, exposure classification is based on the World Heritage List selection criteria and vulnerability is based on site typology. The analysis on 1121 sites, as of March 2021, shows that 35% of natural and 21% of cultural and mixed UNWH sites are exposed to river floods. The risk matrix combining hazard, exposure and vulnerability reveals that 2% of UNWH is at extremely high risk and 7% at very high risk, mostly in the Europe-North America and Asia-Pacific Regions. The analysis also stresses the need for a systematic collection, update, and storage of georeferenced data for cultural heritage. Further analysis should be carried out at local scales, with a priority for higher risk sites to better estimate hazard and vulnerability at a higher spatial resolution.